Diagnosis and Management of Dystonia. Issue 4 (August 2016) - Shanker, Vicki; Bressman, Susan B.
Abstract : ABSTRACT: Purpose of Review: This article highlights the clinical and diagnostic tools used to assess and classify dystonia and provides an overview of the treatment approach. Recent Findings: In the past 4 years, the definition and classification of dystonia have been revised, and new genes have been identified in patients with isolated hereditary dystonia (DYT23, DYT24, and DYT25). Expanded phenotypes were reported in patients with combined dystonia, such as those with mutations in ATP1A3 . Treatment offerings have expanded as there are more neurotoxins, and deep brain stimulation has been employed successfully in diverse populations of patients with dystonia. Summary: Diagnosis of dystonia rests upon a clinical assessment that requires the examiner to understand the characteristic disease features that are elicited through a careful history and physical examination. The revised classification system uses two distinct nonoverlapping axes: clinical features and etiology. A growing understanding exists of both isolated and combined dystonia as new genes are identified and our knowledge of the phenotypic presentation of previously reported genes has expanded. Genetic testing is commercially available for some of these conditions. Treatment options for dystonia include pharmacologic therapy, chemodenervation, and surgical intervention. Deep brain stimulation benefits many patients with various types of dystonia.